Emprego de técnica dedicada de análise de imagem na avaliação do produto GT no desempenho da floculação - Moreno, Pamela [UNESP] (2015)
Flocculation is a paramount step in water treatment for public supply, in addition, is essential to remove the particulate material. The knowledge about the distribution of the flocculent particles size becomes important to the flocculent particles size becomes important to understand the process of flocs removal and the treatment technology that must be adopted. In this study was evaluated the product of the average velocity gradient flocculation (Gf) by time of flocculation (Tf), GT is also defined as Camp number (NC), according to the particle size distribution (PSD). In this case, the technique of image treatment was used to obtain the PSD and the others representatives parameters. Wete investigated different values of NC (18000, 24000, 36000, 54000 e 72000) for evaluation of the sedimentation efficiency in different associated velocities (0,5;, 1,5; 2,5; 3,5 e 5.0 cm/min). The results show that NC is fundamental for the sedimentation performance in all velocities. For the same NC the average of the velocity gradient was determinant, being one of the best results for Gf= 20 s. If the velocity of sedimentation is constant (2,5 cm/min) is possible to conclude that the turbidity removal efficiency maintain 70% fir Cam numbers around 24000, 36000 and 54000. In the order hand, for extrem values 18 and 72 thousand exist a reduction of efficiency. In relation with PSD, is possible to analyze your characteristic parameter β that is sensible according with the provided energy. In conclusion, the case of study show that the increase of provided energy during flocculation results in reduction of dynamic alteration about particle size distribution, establishing inverse proportion between energy and variation of the chaacteristic parameter β. This happens due to flocs action of rupture that contributes to reach the equilibrium state of the flocculent particles in less time of flocculation. Moreover,high values of Gf and NC imply high values...